Szkoła jako miejsce tworzenia relacji społecznych - Strykowska-Nowakowska, Justyna (Pedagogika Społeczna Nova, 2025)
This paper explores the concept of school as a place for building social relationships, a rapidly developing perspective in the study of school activities. The paper is divided into two parts: theoretical and research-based. The first part presents and discusses the meanings and understandings of the terms: relationships, ties, and social interactions in the social sciences. The second part features qualitative research focused on diagnosing social relationships within schools, conducted from the perspectives of teachers, students, and parents.